Impacts of Ionizing Radiation on the Different Compartments of the Tumor Microenvironment - Leroi, Natacha; Lallemand, François; Coucke, Philippe; Noel, Agnès; Martinive, Philippe (Frontiers in Pharmacology, 2016)
Radiotherapy (RT) is one of the most important modalities for cancer treatment. For many years, the impact of radiotherapy on cancer cells has been extensively studied. Recently, the tumor microenvironment emerged as one of the key factors in therapy resistance. Radiotherapy is known to influence and modify diverse components of the tumor microenvironment. Hence, we intent to review data from the literature on the impact of low and high single dose, as well as fractionated radiotherapy on host cells (endothelial cells, fibroblasts, immune and inflammatory cells) and the extracellular matrix. Optimizing the schedule of RT (i.e. dose per fraction) and other treatment modalities is a current challenge. A better understanding of the cascade of events and tumor microenvironment remodeling following radiotherapy would be helpful to design optimal treatment combination.